Circulating Tumor Cell Count Can Be a Useful Prognostic Factor in Lung Resection via Cardiopulmonary Bypass - Masaki Hashimoto (Case Reports in Oncology, 2017)
Tumor resection with cardiopulmonary bypass (CPB) remains controversial in the field of oncology. Here, we present a 57-year-old male patient with locally advanced squamous cell carcinoma. The tumor was located in the left hilum and invaded the left atrium. Complete resection, left pneumonectomy combined with partial left atrium resection, was achieved using CPB. We evaluated the circulating tumor cell (CTC) counts, as a surrogate for micrometastasis, in peripheral blood and the CPB circuit. Both CTC counts were 0, which could indicate local disease without micrometastasis. CTC count may be a useful indicator for tumor resection with CPB in lung cancer.